Selection of sunflower inbreds based on stability analysis using AMMI model: Selection of sunflower inbreds based on stability analysis using AMMI model - VINEETA KAILA (Journal of Oilseeds Research, 2023)
Stability analysis for seed yield and oil content using AMMI model was carried among 44 sunflower inbreds evaluated in four growing seasons from spring 2018 to 2021. Higher variation was observed among the inbreds for seed yield in comparison to oil content across the years. As per AMMI analysis the genotype x environment interaction was partitioned into three principal component axis among which IPCA1 explained 48.7 % and 59.1% variation for seed yield and oil content respectively. Inbreds LTRR 341, RHA 265, P 147R, RHA 83R6, OPH 73 and P 107R P1 were found stable for seed yield whereas, OPH 98, OPH 99, OPH 118, OPH 90, OPH 73 and LTRR 341 were found stable for oil content.